Enhancement of Power Output by using Alginate Immobilized Algae in Biophotovoltaic Devices. Issue 1 (December 2017) - Ng, Fong-Lee; Phang, Siew-Moi; Periasamy, Vengadesh; Yunus, Kamran; Fisher, Adrian
Abstract We report for the first time a photosynthetically active algae immobilized in alginate gel within a fuel cell design for generation of bioelectricity. The algal-alginate biofilm was utilized within a biophotovoltaics (BPV) device developed for direct bioelectricity generation from photosynthesis. A peak power output of 0.289 mWm−2 with an increase of 18% in power output compared to conventional suspension culture BPV device was observed. The increase in maximum power density was correlated to the maximum relative electron transport rate (rETRm). The semi-dry type of photosynthetically active biofilm proposed in this work may offer significantly improved performances in terms of fuel cell design, bioelectricity generation, oxygen production and CO2 reduction.